Lymphokine activated killer cells from peripheral blood mononuclear cells of endometriosis of patients improve cytotoxicity to endometriosis cell culture (Faculty of Medicine Universitas Indonesia, 2011)
Background: To assess the increased cellular immunity of Peripheral Blood Mononuclear Cells (PBMC) derived LAK cells from endometriosis patients towards endometriosis cell cultures after stimulation with IL-2. Methods: This study is a quasi-experimental study of pre and post treatment using controls. Phenotype evaluation ofÂ CD3+CD4+, CD3+CD8+ and CD56+ effector cells of PBMC from endometriosis patients and controls was performed. Cytotoxicity test of PBMC from endometriosis patients and control towards Daudi, K562 cell line and endometriosisÂ cell cultures using 51Chromium release assay was also carried out. Results: Phenotype evaluation of PBMC from endometriosis patients (n = 10) and controls (n = 6) were done prior to and after IL-2 stimulation. Before IL-2 stimulation, CD3+CD4+, CD56+ from endometriosis group (n = 10) tend to be lower than control (n=6) whereas CD3+CD8+ were higher in endometriosis group than controls. After IL-2 stimulation, CD3+ CD8+, CD56+ of PBMC from endometriosis group were significantly increased (p < 0.05). Cytotoxicity test revealed a significant increase (p < 0.05) in both PBMC's effector cells from endometriosis and control group towards target cells, Daudi, and K562 cell lines after IL-2 stimulation. PBMC's effector cells cytotoxicity from both endometriosisÂ and control towards target endometriosis cell cultures were also elevated after IL-2 stimulation. Conclusion: LAK cells derived IL-2 stimulated PBMC from endometriosis patients increased cellular immunity towards endometriosis cell cultures. (Med J Indones 2011; 20:87-93)